A STUDY OF LEARNING STYLE PREFERENCES OF ALL FEMALE STUDENTS IN UNIVERSITY LEVEL (A Case Study in one of Islamic University in Bandung) - Siti Nuraeni Muhtar (Eltin Journal : Journal of English Language Teaching in Indonesia, 2014)
This research investigated students learning styles of all female students in University Level. The study involved 129 students in one of Islamic University in Bandung. The C.I.T.E Learning Styles Instrument by Joy Reid was used to identify 6 different kinds of Learning Styles. The research questions were as follows: (1) What are the learning styles  possessed by students?, (2) What are the dominant learning styles of Female Students in University Level?, and (3) How do those learning styles influence students’ level of study?.The data percentages show that most of students in each class have visual learning style by the percentage (A:65,21%, B:73,17%, C:66,67%, D:73,91%). The second highest numbers also happens to Kinesthetic learning style  (A:69,56%, B:48,78%, C:59,532%, D:65,22%) and Individual learning style (A:73,91%, B:43,90%, C:47,62%, D:69,56%). From those data, it can be concluded that more than a half female students in that university are visual, kinesthetic and auditory learners. Tactile learnes are only between 40-50 % of students. And the least percentage of students are auditory and group learners. Based on the result, the learning styles of every class are different. The phenomena shows that there are no special kinds of learning styles that can determine level of study.       Keywords: learning style, visual, kinesthetic, auditory,  tactile